2017
DOI: 10.1002/jcp.25784
|View full text |Cite
|
Sign up to set email alerts
|

TNF‐α promotes osteoclastogenesis through JNK signaling‐dependent induction of Semaphorin3D expression in estrogen‐deficiency induced osteoporosis

Abstract: Tumor necrosis factor α (TNF-α)-induced osteoclast formation have been demonstrated to play an important role in the pathogenesis of estrogen deficiency-mediated bone loss, but the exact mechanisms by which TNF-α enhanced osteoclast differentiation were not fully elucidated. The class III semaphorins members were critical to regulate bone homeostasis. Here, we identified a novel mechanism whereby TNF-α increasing Semaphorin3D expression contributes to estrogen deficiency-induced osteoporosis. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Many published studies have described the role of TNF in the development of osteoporosis. For example, TNF/TNFR1 signaling promoted osteoclastogenesis by JNK signaling-induced expression of semaphorin 3D [24]. Another study showed that TNF/TNFR1 signaling suppressed bone formation in estrogen deficiency-induced osteoporosis by inhibiting semaphorin 3B via Wnt/β-catenin signaling [25].…”
Section: Discussionmentioning
confidence: 99%
“…Many published studies have described the role of TNF in the development of osteoporosis. For example, TNF/TNFR1 signaling promoted osteoclastogenesis by JNK signaling-induced expression of semaphorin 3D [24]. Another study showed that TNF/TNFR1 signaling suppressed bone formation in estrogen deficiency-induced osteoporosis by inhibiting semaphorin 3B via Wnt/β-catenin signaling [25].…”
Section: Discussionmentioning
confidence: 99%
“…JNK signaling activated by the inflammatory cytokines TNF-α and IL-1 induces cell-cell fusion to form osteoclasts and enhances osteoclast survival, respectively [ 69 , 70 , 71 ]. IL-17A facilitates autophagic activity of osteoclast precursors and promotes osteoclastogenesis via activating the RANKL-JNK pathway [ 72 ].…”
Section: Jnk Signaling In Osteoclastsmentioning
confidence: 99%
“…JNK signaling also induces the expression of the calcium/calmodulin-dependent protein kinase (CaMK), c-Fos, and NFATc1, which are involved in the maintenance of osteoclast lineage commitment [ 65 , 75 ]. Semaphorin 3D is a downstream target of JNK signaling and is involved in stimulating TNF-α-induced osteoclastogenesis [ 69 ].…”
Section: Jnk Signaling In Osteoclastsmentioning
confidence: 99%
“…The therapeutic targets are mainly focused on the inhibition of osteoclast activity and the promotion of osteogenesis. Therefore, the repression of osteoclastogenesis and bone resorption activity are of great significance in the prevention and treatment of osteoporosis . We found that ABP can decrease the expression of NFATc1, Integrin β3, TRAcP, and CTSK via suppressing the phosphorylation of MAPK pathways, which inhibited RANKL induced osteoclast differentiation and function (Figure ).…”
Section: Discussionmentioning
confidence: 86%